Ecthyma gangrenosum as a serious complication of Pseudomonas aeruginosa infection in departments of pediatric oncology - Gałązka, Przemysław; Kaczor, Patryk; Kałużny, Krystian; Leis, Kamil (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
In most cases ecthyma gangrenosum is a consequence of Pseudomonas aeruginosa bloodstream infection in immunodeficient patients. This bacterium is characterized by multi-drug resistance and has a number of mechanisms that allow it to survive even in extreme conditions. The disease is characterized by an aggressive course involving the skin and mucous membranes, leading to ulceration with signs of necrosis within 12 to 24 h. Treatment includes targeted antibiotic therapy and surgical cleansing of the wound. If the perianal area is occupied, a colostomy may be performed. Prevention of bacterial infections involves taking special precautions when handling a patient with immunodeficiency.